Legal Protection of Tongkonan Traditional Land Management in The Traditional Community of Tana Toraja - Bernike Mangi; Abrar Saleng; Andi Suriyaman Mustari Pide (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
Legal Protection of tongkonan Traditional land management in thetraditonal community of Tana Toraja. Guided by Abrar Saleng, and Andi Suriyaman Mustari Pide. This study aims to explain and analyse form of customary land management in Tongkonan on customary community of Tana Toraja and to explain and analyse possible implications occurred if customary land management in customary community of Tana Toraja were not protected. This research was conducted in the Tana Toraja District seeing several gaps that can eliminate MHA culture from various actions of several parties. This study uses empirical studies. Data collection was carried out by interviews and then analyzed qualitatively. Tongkonan customary land is managed together by each Tongkonan under the supervision of Tongkonan Layuk and is guided by Aluk Tallu Lolona which plays an important role in maintaining environmental sustainability with the belief that all parts of the land are ancestral heritage that must be preserved as a form of appreciation. The implication occurs if the land of Tongkonan is not protected by law is the loss of the characteristics of the culture of indigenous peoples because of various actions to control the land. Therefore we need regulations to protect the rights of indigenous peoples over their land.